Profil Darah Ikan Kakap Putih ( Lates calcalifer )Yang Diberi Pakan Mengandung (Gracilaria sp.) - Isy Aulia Hanum Sahfitri; Rika Wulandari; Aminatul Zahra (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2021)
Research on the Blood Profile of White Snapper Fish Lates calcalifer Feed Containing Gracilaria sp.. conducted to test materials that have the ability to stimulate hematocrit and differential leukocytes. One of the ingredients contained in Gracilaria sp. is the presence of sulfate polysaccharides. This research was conducted in November 2020. The maintenance of test fish was carried out in floating net cages in Madong Village, Bugis Village, and blood tests were carried out at theLaboratory Marine Biotechnology, Faculty of Marine Science and Fisheries, Raja Ali Haji Maritime University. This research was conducted using a completely randomized design (CRD) method with 4 treatments and 3 replications, with treatment K (Feeding without the addition of Gracilaria sp.), A (Feed with Gracilaria sp. 15 gram / kg of feed), B (Feed with flour of Gracilaria sp. 20 grams / kg of feed), and C (feed with Gracilaria sp. 25 grams / kg of feed). White snapper was fed at satiation treatment 2 times a day for 14 days. The results showed that Gracilaria sp. In feed, it has a significant effect on hematocrit and differential of lymphocyte type leukocytes in white snapper, but does not have a significant effect on monocytes and neutrophils of white snapper.